The origins of early Christian literature contextualizing the New Testament within Greco-Roman literary culture - Walsh, Robyn Faith 1980- (New York University of Cambridge ESOL Examinations, 2021)
The Synoptic gospels were written by elites educated in Greco-Roman literature, not exclusively by and for early Christian communities.
Description based on publisher supplied metadata and other sources
Keywords: Bible.-Gospels-Criticism, interpretation, etc; Electronic books; Hochschulschrift